Grammatical Rules and Analogy in Natural Morphology - Bálint, Rita (Slavica, 2023)
Analogy plays a significant role in problem solving, as well as in decision making, argumentation, perception, generalization, memory, creativity, invention, prediction, emotion, explanation, conceptualization, and communication. Analogy is important not only in ordinary language and common sense (where proverbs and idioms give many examples of its application) but also in science, philosophy, law, and the humanities. Still, in linguistics it causes many uncertainties. The main purpose of this work is to study and examine the principles of Natural Morphology on the historical change of Bulgarian verbs. This study is a summary of how grammatical rules and analogy, and their antithesis dissolve in the theory of Natural Morphology. The focus of the paperis the historical variation of the Bulgarian Aorist.